Om de döda inget annat än gott? En kritisk granskning av den avlidnes rättsliga skydd mot att bli förtalad - Romedahl,Sophie (2021)
Defamation of a deceased individual has been criminalized in Sweden since the entry into force of the Swedish Criminal Code (SFS 1962:700). However, this crime has been given a somewhat suppressed position in the Swedish legal system. At least, until the historical press conference on the 10th of June 2020, where the decision to close the preliminary investigation about the assassination of Olof Palme, was announced. In the following public debate, critical voices were raised regarding the prosecutor’s decision to name the suspected deceased murderer. The designation of a deceased individual who has no possibility to defend himself has, in the eyes of many people, been perceived as offensive. Deceased individuals’ protection against defamatory accusations, once again became a topic of discussion, when the dramatization The unlikely murderer was released on Netflix. The series is based on the same theory as the one presented at the press conference. Namely that Stig Engström (often referred to as “Skandiamannen”) is the murderer of Olof Palme. In the light of these events, the purpose of this thesis is to critically examine the level of protection against defamation, which the Swedish legal system offers to deceased individual’s. The essay results in the following conclusions. The interest of protecting a deceased individual’s honor, is in many cases considered to be subordinate to the interest of an extensive freedom of speech. A suitable example here is the designation of Stig Engström as the suspected murderer of Olof Plame, made by the prosecutor at the press conference. The widespread public interest in why, one of the world’s largest murder investigations was discontinued, was considered to be of greater interest. Relevant aspects of the assessment are among other things, whether a long time has passed since the time of death or if the memory of the deceased lives on, in the memory of relatives. Furthermore, regarding the possibilities of commencing a prosecution, the main rule is private prosecution. Public prosecution should only occur in exceptional cases. However, the circle of people who can commence a prosecution according to chapter 20 section 13 The Code of Judicial Procedure, is extremely limited. At the same time, there is no real motivation for this.
Keywords: Processrätt; statsrätt; straffrätt; förtal av avliden